An Investigation into the Challenges and Strategies Utilization in Academic Writing: A Case Study of Indonesian Postgraduate Students - Muryani, Rera Nadian; Romadhon, M Galuh Elga; Mustofa, Mutmainnah (Universitas Hamzanwadi, 2024)
This study explores into the challenges encountered by postgraduate students in the realm of academic writing,along with the strategies they employ to tackle these hurdles and the resources aiding their writing process.Employing narrative inquiry as the research design, the study aimed to facilitate a comprehensive explorationof these issues. The participants consisted of ten postgraduate students enrolled at a private university inIndonesia. The research methodology involved conducting interviews with these students to uncover thestrategies and tools utilized by English Master's degree students to achieve success in academic writing.Primary difficulties identified included challenges in organizing coherent content, sourcing relevant referencesto bolster arguments, navigating spatial constraints when expressing ideas, and accurately interpreting data.The findings revealed that digital resources, such as scholarly websites and databases, emerged as the primarysources for accessing journals and articles. In contrast, printed materials played a diminished role due to theiroutdated nature. The study underscores the importance of understanding these inherent challenges in writingand leveraging available strategies and resources to enhance writing skills, thereby enabling postgraduatestudents to produce high-quality research papers.